PEMBERDAYAAN IBU-IBU RUMAH TANGGA MUSLIMAH DALAM MENGELOLA SAMPAH MELALUI E-MEDIA BERWAWASAN SAINS TEKNOLOGI - Eni Setyowati (State Institute of Islamic Studies (IAIN) Salatiga, 2015)
The research aimed to empower the Muslim housewife’s understanding and skill in Tulungagung in waste management through Science and Technology e-media. The subjects of the empowerment are the housewives in Tanggung, Tanjungsari, and Jabon villages. The methods of the empowerment are formal and non-formal approaches, training, and implementation. The analysis was carried out using gain score normalized to analyze the value of understanding and skill in waste management before and after the empowerment. The results indicated that e-media can improve the housewife’s understanding (0,5) and it can improve the housewife’s skill (0,68). This showed that e-media can be as one of educational media in waste management.